Politik Luar Negeri Indonesia dan Malaysia Terhadap China di Era Perang Dingin - Nabil Ahmad Fauzi (Insignia: Journal of International Relations, 2014)
Since the proclamation on the 1st October 1949, the People's Republic of China has gained an important role in international relations after World War II. The success of communism conquered China, has changed the dynamics of competition between the United States and the Soviet Union that lead the Western Bloc and the Eastern Bloc. The situation has forced the newly independent states in this era, like Indonesia and Malaysia, to determine their position. In addition to facing the same international politics pressures, the two countries also have relations in the domestic issues related to China, namely the existence of the local Communist Party and ethnic of "Chinese overseas". The external and domestic factors that ultimately affect the choice of the countries' foreign policy towards China. This article attempts to identify and explore the factors that influence the similarities and differences in Indonesia and Malaysia foreign policy towards China using the approach threat perception, leader perception and domestic legitimacy within the framework of neo-classical realism. This article is expected to provide scientific contributions to understanding the comparison of Indonesia and Malaysia foreign policy towards China. Keywords: Indonesia and Malaysia foreign policy, the existence of China, Cold War era, threatperception, leader perception, domestic legitimacy, neo-classical realism